THE RELATIONSHIP BETWEEN MOTIVES AND COMMUNITY WORK WITH THE SUCCESS OF COVID-19 VACCINATION AT PUSKESMAS DARUSSALAM BIG ACEH - Rika Dewi; Putri Ilham Sari (Jurnal Syntax Transformation, 2023)
Covid-19 is an infectious disease caused by a new type of coronavirus with the most common symptoms being fever, weakness, coughing, convulsions and diarrhea. The disease caused by this new virus became known after the discovery of an outbreak in Wuhan, China, in December 2019 and now the virus has spread to many countries around the world. According to WHO in March 2022 the number of cases of corona virus infection in the world has reached 441,186,679 people. The purpose of this study was to determine the relationship between motives and people's work on the success of the Covid-19 Vaccination at the Darussalam Aceh Besar Health Center. This research method is an analytic survey research using a cross sectional approach, the sampling technique was accidental sampling with a total sample of 49 people. The research instrument is a questionnaire. Data analysis used univariate and bivariate analysis with the SPSS statistical program. Research Results: The statistical test results with the Chi-square test showed a p-value of 0.706 > 0.05, so there was no motive relationship to the success of the Covid-19 vaccination in the community at the Darussalam Aceh Health Center The Great Year is 2022. The results of the statistical test using the Chi-square test show a p-value of 0.020 <0.05, so there is a work relationship with the success of the Covid-19 vaccination in the community at the Darussalam Aceh Besar Health Center. The conclusion is that there is an influence of work on the success of the Covid-19 vaccination, because people who work are usually required to obey orders from their superiors and follow government regulations. Suggestions so that people can understand the dangers of the Covid-19 virus and can comply with vaccines as recommended by the government.